The effects of HIV Protease Inhibitors (Lopinavir/Ritonavir) on the non-oxidative pathways of glucose metabolism - Fisher, Tarryn-Lee (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.